Between French Soft Power and Latin American Development: the “Geopolitical Urban Planning” of the Sixties and the Seventies - Clément Orillard (Iberoamericana. América Latina - España - Portugal, 2020)
The Francophile tradition in Latin American urban planning evolved in the sixties and seventies. In France, the State created not only new public but also parapublic organisms in charge of developing urban analysis and planning. One of the most important, which oversaw the Paris region, also developed many missions in Latin America. The study of the first missions in Argentina, Brazil, and Bolivia shows that they were at the conjunction of two movements: the policy of soft power and economic expansion of the French government and the new “developmentalist” economic planning policies of the Latin American governments.